HIV-Related Lymphoproliferative Diseases in the Era of Combination Antiretroviral Therapy - Castelli, Roberto (Cardiovasc Hematol Disord Drug Targets, 2020)
HIV-positive patients have a 60- to 200-fold increased incidence of Non-Hodgkin Lymphomas (NHL) because of their impaired cellular immunity. Some NHL are considered Acquired Immunodeficiency Syndrome (AIDS) defining conditions. Diffuse large B-cell Lymphoma (DLBC) and Burkitt Lymphoma (BL) are the most commonly observed, whereas Primary Effusion Lymphoma (PEL), Central Nervous System Lymphomas (PCNSL), Plasmablastic Lymphoma (PBL) and classic Hodgkin Lymphoma (HL) are far less frequent. Multicentric Castleman disease (MCD) is an aggressive lymphoproliferative disorder highly prevalent in HIV-positive patients and strongly associated with HHV-8 virus infection. In the pre-Combination Antiretroviral Therapy (CART) era, patients with HIV-associated lymphoma had poor outcomes with median survival of 5 to 6 months. By improving the immunological status, CART extended the therapeutic options for HIV positive patients with lymphomas, allowing them to tolerate standard chemotherapies regimen with similar outcomes to those of the general population. The combination of CART and chemotherapy/ immuno-chemotherapy treatment has resulted in a remarkable prolongation of survival among HIV-infected patients with lymphomas. In this short communication, we briefly review the problems linked with the treatment of lymphoproliferative diseases in HIV patients. Combination Antiretroviral Therapy (CART) not only reduces HIV replication and restores the immunological status improving immune function of the HIV-related lymphomas patients but allows patients to deal with standard doses of chemotherapies. The association of CART and chemotherapy allowed to obtain better results in terms of overall survival and complete responses. In the setting of HIV-associated lymphomas, many issues remain open and their treatment is complicated by the patient’s immunocompromised status and the need to treat HIV concurrently.